2009
DOI: 10.1016/s0140-6736(09)60404-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of tumour-responsive T cells as cancer treatment

Abstract: The stimulation of a tumour-specific T-cell response has several theoretical advantages over other forms of cancer treatment. First, T cells can home in to antigen-expressing tumour deposits no matter where they are located in the body—even in deep tissue beds. Additionally, T cells can continue to proliferate in response to immunogenic proteins expressed in cancer until all the tumour cells are eradicated. Finally, immunological memory can be generated, allowing for eradication of antigen-bearing tumours if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 126 publications
(111 reference statements)
0
110
0
2
Order By: Relevance
“…Even the promising approach of adoptive transfer of tumor-specific T cells against malignant cells does not consistently yield satisfying results. [57][58][59][60] Several factors for inducing immune defects in T cells have been proposed, including the immunosuppressive setting of the tumor microenvironment. 3,61 An emerging concept of the tumor microenvironment is the suppression of an adaptive immune response by tumor metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Even the promising approach of adoptive transfer of tumor-specific T cells against malignant cells does not consistently yield satisfying results. [57][58][59][60] Several factors for inducing immune defects in T cells have been proposed, including the immunosuppressive setting of the tumor microenvironment. 3,61 An emerging concept of the tumor microenvironment is the suppression of an adaptive immune response by tumor metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…36, 44 Ramakrishnan et al found that the chemotherapeutic agents doxorubicin, paclitaxel and cisplatin increased tumor cell permeability to granzyme B (GrzB), leading to their increased sensitization to CTLs. Upregulation of manose 6 phosphate (M6P) led to increased GrzB uptake.…”
Section: Discussionmentioning
confidence: 99%
“…1 They are frequently present in solid human tumors, 2 and their role in different types of cancers has been controversial. The presence of TILs correlates with a better prognosis in several types of cancer, and each T-lymphocyte subset has a unique role in the antitumor response.…”
Section: Introductionmentioning
confidence: 99%